2020
DOI: 10.3389/fphar.2020.567852
|View full text |Cite
|
Sign up to set email alerts
|

Dibenzazepine Attenuates Against Cisplatin-Induced Nephrotoxicity in Rats: Involvement of NOTCH Pathway

Abstract: Cisplatin is one of the standard anti-cancer agents that are used to treat variety of solid tumors. Nevertheless, due to the accumulation of cisplatin in the renal epithelial cells, nephrotoxicity was found to be the main side effect that limits its clinical use. The current study was conducted to assess the potential nephroprotective effect of dibenzazepine, a Notch inhibitor, against cisplatin-induced nephrotoxicity in rats as well as the possible mechanisms underlying this nephroprotection. The rats were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 72 publications
3
13
0
Order By: Relevance
“…Caspase-3, an executioner of apoptosis is considered an index of apoptosis 37 . Consistent with previous investigations Abd El-Rhman et al 67 stated that the CDDP-treated rats had a 483.7 percent rise in caspase-3 levels when compared to the control rats. In comparison to the CDDP group, pretreatment of CDDP-injected rats with Dibenzazepine dramatically lowered caspase-3 levels by 43.2%.…”
Section: Discussionsupporting
confidence: 90%
“…Caspase-3, an executioner of apoptosis is considered an index of apoptosis 37 . Consistent with previous investigations Abd El-Rhman et al 67 stated that the CDDP-treated rats had a 483.7 percent rise in caspase-3 levels when compared to the control rats. In comparison to the CDDP group, pretreatment of CDDP-injected rats with Dibenzazepine dramatically lowered caspase-3 levels by 43.2%.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous investigations Abd El-Rhman et al 64 stated that the CDDP-treated rats had a 483.7 percent rise in caspase-3 levels when compared to the control rats. In comparison to the CDDP group, pretreatment of CDDP-injected rats with Dibenzazepine dramatically lowered caspase-3 levels by 43.2%.…”
Section: Immunohistochemistry Analysissupporting
confidence: 90%
“…In this study, the serum creatinine and urea levels increased significantly in the cisplatin-treated mice, which confirmed the nephrotoxicity of cisplatin as reported by previous studies on rat models. 22–24 In addition, cisplatin also led to severe histopathological changes in the kidneys, including vacuolization of renal tubular epithelial cells, inter-tubular capillary hyperemia, glomerular mesangial cell proliferation, inflammatory cell infiltration, glomerular atrophy and focal renal hemorrhage. Furthermore, in this study, cisplatin induced liver damage, as indicated by the high AST and ALT levels, as well as hydro-degeneration and fatty degeneration of liver cells in the treated mice, which was consistent with the results of previous studies.…”
Section: Discussionmentioning
confidence: 98%